Application of Waste Oil as An Effective Construction Material with Reclaimed Asphalt Pavement : A Review - Lahre, Nidhi; Supe, Jayant (International Journal of Scientific Research in Civil Engineering, 2020)
The current asphalt pavement industry faces two major issues. These two main issues are the increasing call for eco-friendly asphalt mixtures and the charges of raw materials. The usage of cultivated asphalt pavement will be a key effort to reduce the prices of aggregates and bitumen in the ultimate mixture. On the other hand, the main trial for implementing RAP (Reclaimed Asphalt Pavement) is to overcome quality issues. RAP doesn’t perform like a new pavement since it is an old material and needs to be upgraded. This puts forward the necessity for extra practices like consuming of rejuvenating agents. Since bitumen drops its oily components when it ages, the use of oil-containing additives can be effective. In this study, two types of waste oils were used to revitalize aged asphalt mixture. In this paper we are presenting review of journals a research performed in past related to our subject.
Keywords: Reclaimed Asphalt Pavement; Eco-Friendly Asphalt Mixtures